2018
DOI: 10.1021/acsanm.8b01340
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and Bactericidal Properties of a Wettability-Controlled Artificial Nanostructure

Abstract: The adhesion behavior and bactericidal properties of the nanostructured surface of Si nanopillar array, which mimicked a cicada wing surface, were evaluated using Escherichia coli. Wettability of the nanostructured surface was controlled by using self-assembled monolayer (SAM). The adhesion behavior was strongly dependent on the wettability of the surface and whether it was a nanostructured or a flat surface. The number of adhered cells on the nanostructured surface was higher than that on the flat Au surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…On the bactericidal property test, the Si nano-pillar array substrate was fabricated and used as an articial nanostructure. Our group had reported that Si nano-pillar arrays could be obtained by colloidal lithography and metal-assisted chemical etching (MacEtch), 15,31 which allow controlling the nanopillar array dimensions. The gap of the nano-pillar was controlled by changing the diameter of PS beads.…”
Section: Preparation Of Glass and Si Nano-pillar Array Substratementioning
confidence: 99%
See 4 more Smart Citations
“…On the bactericidal property test, the Si nano-pillar array substrate was fabricated and used as an articial nanostructure. Our group had reported that Si nano-pillar arrays could be obtained by colloidal lithography and metal-assisted chemical etching (MacEtch), 15,31 which allow controlling the nanopillar array dimensions. The gap of the nano-pillar was controlled by changing the diameter of PS beads.…”
Section: Preparation Of Glass and Si Nano-pillar Array Substratementioning
confidence: 99%
“…Our group reported that the number of attached cells depended on presence or absence of nanostructure and the surface wettability. 15 The number of attached cells increased with the contact angle for water (WCA: water contact angle) and that on the nanostructured surface was about twice compared to the at surface at the same WCA. To develop an application in the eld of sanitary engineering, it is important to increase the number of attached cells to improve the bactericidal and antibacterial properties of the nanostructured surface.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations